(untitled) (International Journal of Automation and Smart Technology, 2025)
This paper provides a new design and automation concept for tertiary buildings in mixed mode ventilation system with combined functions of mechanical air conditioning and natural ventilation. It aims to make use of simple automation design and set-up to significantly reduce the energy consumption while keeping optimum occupants’ comfort. A prototype architectural design of the building aimed at maximizing the passive cooling potential is presented in this paper. The automation system follows a simple control outline where input parameters are fed into a programming control and the system yields the necessary output condition. The system runs in two control operations—schedule-based and event-based—with independent input parameters and with output conditions identified as natural ventilation, full mechanical ventilation, and partial mechanical ventilation. The specific controller, sensors, and actuators for implementing the building automation system were identified. The whole automation concept and design was programmed in an automation software and was simulated to look at the possible system scenarios and results. Results show that a cost saving of as much as Php 246,874.00 per year could be achieved.